Effects of Auditory Frequency Stimulation on Balance and Rehabilitation Outcomes in Patients With Stroke: A Randomized Case‐Control Study - Ruijin Chen; Lihua Jin; Jin Song; Juchuan Dong; Yongmei Li (Brain and Behavior, 2025)
ABSTRACT Background Although the role of sensory input in maintaining balance is well established, the effects of various auditory frequency stimulations, such as binaural beat stimulation (BBS), on patients with central nervous system injuries, particularly those who have experienced a stroke, remain inadequately understood. Methods This randomized case‐control study compared the functional outcomes between patients with stroke undergoing BBS during rehabilitation training and those receiving traditional music therapies. The assessed primary outcomes included balance function, balance confidence, lower‐limb function, and activities of daily living, cognitive abilities, and depression scores. Subsequently, correlations between outcome parameters were analyzed. Results A total of 27 patients with stroke completed the study protocol (BBS n = 15, control n = 12). Post‐intervention analyses revealed improvements in balance‐related indicators, particularly the scores of the Berg Balance Scale (BBSc) and Mini‐Balance Evaluation Systems Test (Mini‐BESTest), across both groups. However, the Barthel index (BI) and Beck depression inventory scores (BDIS) in the BBS group exhibited significantly greater improvements than those in the control group. Correlation analyses indicated that changes in balance‐related scores within the BBS group were associated with improvements in lower‐limb function, mood, and activities of daily living. Conversely, the control group observed correlations among the internal components of the balance‐related scales. Conclusion Appropriate BBS stimulation appears to enhance balance, likely owing to the synergistic effects of music and rhythm. Further research focusing on brain function is necessary to elucidate the mechanisms underlying the therapeutic efficacy of BBS interventions.